Enhancing micro-EDM using ultrasonic vibration and approaches for machining of nonconducting ceramics - Schubert, Andreas (Strojniški vestnik, 2013)
This paper presents the current status of investigation into the micro-EDM process with ultrasonic vibration assistance directly applied to the workpiece and indirectly applied high-intensity ultrasonic to the dielectric in metallic materials as well as in the machining of electrically nonconductive ceramic materials. Using ultrasonically aided micro-EDM, the process speed can be raised by up to 40%, enabling bores of less than 90 m in diameter with aspect ratios >40 for metallic materials. The modified setup using the assisting electrode principle allows for machining of an aspect ratio >5 for nonconductive ceramic materials, leading to new possibilities for the design and manufacture of complex, high-accuracy micro parts in high-performance engineering materials.
Keywords: ceramic; ceramics; electro discharge machining; elektroerozijska obdelava; keramika; micro machining; mikroobdelava; natančna obdelava; ultrasonic; ultrasound; ultrazvok; visokozmogljivi materiali